Measurement of alkaline phosphatase of intestinal origin in plasma by p-bromotetramisole inhibition. - Kuwana, T (1991)
L-p-bromotetramisole was used to inhibit non-intestinal alkaline phosphatase (of liver or bone origin) (EC 3.1.3.1; ALP) in plasma, and intestinal ALP was measured from the uninhibited activity. The method of determination is convenient and correlated well with measurement by immunocapture assay. If carried out in parallel with wheat-germ lectin precipitation of bone ALP, subtraction of intestinal ALP activity from that of non-bone ALP in the supernatant can be used to measure the ALP that originates from the liver in men and non-pregnant women.